Evaluation of learning environment among Nursing undergraduates in state universities, Sri Lanka - Patalee Jayaweera; Abisheka Thilakarathne; Madushanka Ratnayaka; Tharangi Shashikala; Rushani Arachchige; Lahiru Sandaruwan Galgamuwa; Nimantha Karunathilaka; Thamara Amarasekara (BMC, 2021)
Abstract Background The learning environment is a vital part of the undergraduate curriculum which enable to delivery of quality education in the stipulated time. Therefore, this study aimed to evaluate the learning environment among BSc. Nursing undergraduates in Sri Lankan state universities. Methods A descriptive cross-sectional study was conducted among 161 final year BSc. Nursing undergraduates in six state universities. Socio-demographic characteristics were collected using a self-administered questionnaire. The Dundee Ready Educational Environment Measure (DREEM) questionnaire was used to evaluate the learning environment in Perception of learning (SPL), Perceptions of teaching (SPT), Academic self-perceptions (SASP), Perceptions of the atmosphere (SPA), and Social self-perceptions (SSP). Based on the SPL, SPT, SASP, SPA, and SSP domains, the overall score of learning environment was ranged from 0 to 200 and then the overall score was classified into four categories such as poor (0-50), many problems (51-100), more positive than negative (101-150) and excellent (151-200). One-way Analysis of Variance (ANOVA) and t-test were used to determine the difference in the subscales and the overall scale. Results The mean age of the students was 24.9 ± 0.9 years. The overall score of the learning environment was 127.1 ± 14.3. Student's Perception of learning showed the highest mean score of 31.1 ± 3.9 while the social self-perception showed the lowest score (mean 16.4 ± 3.1). A significant group effect was observed in SPL and SPT subdomains among state universities while no significant group effect was observed in other subdomains. Furthermore, participating in extracurricular activities, travelling time to the faculty, and gender were observed as associated factors for the learning environment among BSc. Nursing undergraduates in state universities. Conclusions Although the overall learning environment of BSc. Nursing undergraduates in state universities in Sri Lanka was within more positive than negative category, none of the university reaches to the excellent category. Therefore, each university should have improved their subdomains of learning environment to reach excellent category through addressing the gaps of curricular and extracurricular activities in the future.